Multiplex Sensing Electronic Skin Based on Seamless Fully Printed Stretchable Piezoelectric Devices. Issue 1 (4th December 2022) - Alique, Marc; Moya, Ana; Otero, David; Kreuzer, Martin; Lacharmoise, Paul; Murillo, Gonzalo; Simao, Claudia Delgado
Abstract: Wearable skin mountable devices, more than flexibility, require conformability, stretchability, and a high water vapor transmission rate, so that the perspiration processes are not blocked, to assure comfort and stability of use in contact with living bodies. Skin mountable stretchable devices with piezoelectric devices have been reported, based on the integration of polyvinylidene fluoride foils with discrete electrodes and stretchable substrates, and show potential in revolutionizing medical devices for remote monitoring applications. However, the electrodes and active layer are usually not stretchable, only the carrier substrate. The study reports the full description of a novel fully printed stretchable piezoelectric device, printed directly over a stretchable polymer foil of thermoplastic polyurethane. The stability of the response of the stretchable piezoelectric devices is used as movement sensors through their output potential. An electronic skin based on a fully printed circuit with a matrix of 15 all‐printed piezoelectric devices is prepared and investigated and used directly mounted on different body parts, and the real‐time monitoring of movements are recorded and analyzed. Abstract : A piezoelectric device circuit directly printed on a stretchable substrate is here described for the first time and investigated in wearable applications. Novel insights on printed piezoelectric devices are described with the elucidation of a polyvinylidene fluoride with trifluoroethylene polymer structure in the multilayer fully printed stretchable piezoelectric device and the demonstration of a 15‐device array circuit as a multiplex sensing electronic skin for body movement monitoring.